EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TAI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Ernawati Hasibuan (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe effectiveness of using cooperative learning model of TAI (Team Assisted Individualization) type on mathematical problem solving ability on the topic beams at the eighth grade students of SMP Negeri 1 Huristak. The research was conducted by using experimental method 32 students as the sample and they were taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using TAI type was 3.71 (very good category) and b) the average of students’ mathematical problem solving ability on the topic beams before using TAI type was 56.31 (fair category) and after using TAI type was 83.69 (very good category)). Furthermore, based on inferential statistic by paired sample ttest using, it could be found the significant value was less than 0.05 (0.000<0.05). It means, cooperative learning model of TAI (Team Assisted Individualization) type was effective on mathematical problem-solving ability on the topic beams at the eighth grade students of SMP Negeri 1 Huristak.